The Effects of Whole-Body Photobiomodulation Light-Bed Therapy on Creatine Kinase and Salivary Interleukin-6 in a Sample of Trained Males: A Randomized, Crossover Study - Ghigiarelli, Jamie J.; Fulop, Andras M.; Burke, Adam A.; Ferrara, Anthony J.; Sell, Katie M.; Gonzalez, Adam M.; Pelton, Luke M.; Zimmerman, Jamie A.; Coke, Shaquille G.; Marshall, Dennis G. (Frontiers in Sports and Active Living, 2020)
Photobiomodulation therapy (PBMT) can be applied to the whole body as compared to the application of using single hand-held devices that isolate a smaller muscle area. The purpose of this study was to examine the effects of an acute dose of whole-body PBMT pre- and post-high-intensity resistance training on creatine kinase (CK) and salivary interleukin-6 (IL-6) in a sample of trained males. Twelve males (31 ± 8.3 yr, 177.2 ± 5.4 cm, and 86.0 ± 7.5 kg) were part of a randomized, counterbalanced, cross-over design, whereby each participant performed a high-intensity resistance training session that consisted of the bench press, chin-up, and repeated sprints on two separate occasions. Each participant was assigned to either the PBMT or control condition on two separate weeks, with a 10-day washout period between the weeks. Creatine kinase was measured at baseline, 24 hours (hrs), 48 hrs, and 72 hrs post-exercise. Salivary IL-6 was measured at baseline, 60 minutes (min), 90 min, and 120 min. A paired t-test showed no significant difference (p = 0.669) in the area under the curve (AUC) for CK during the PBMT (191.7 ± 48.3) and control conditions (200.2 ± 68.0). A Wilcoxon signed-rank test also showed no significant median difference (p = 0.155) in the AUC for salivary IL-6 during the PBMT (Mdn = 347.7) and control conditions (Mdn = 305.8). An additional Wilcoxon signed-rank test for CK percentage change from 24 hrs to 72 hrs showed the PBMT condition (Mdn = -45%) to have a -18% median difference as compared to the control condition (Mdn = -41%). As such, whole-body PBMT does not significantly reduce the activity of salivary IL-6 or CK concentration during the 24- to 72-hr recovery post-high-intensity resistance training.